Volumetric osseous changes in the completely edentulous maxilla after sinus grafting and lateral bone augmentation: a systematic review. Issue 11 (November 2020) - Coopman, R.; Fennis, J.; Ghaeminia, H.; Van de Vyvere, G.; Politis, C.; Hoppenreijs, T.J.M.
Abstract: The aim of this systematic review was to evaluate the volumetric changes associated with different bone grafting techniques in the completely edentulous atrophic maxilla before dental implant placement. A search was performed according to the PRISMA guidelines. A PICO question was formed, and the PubMed, Scopus, Embase, and Cochrane Library databases were searched, covering the period 2000–2018. Relevant data were extracted from the results regarding study population, surgical details, technical information on volumetric data acquirement, and volumetric outcome after bone augmentation procedures before implant placement. Six articles with a combined population of 84 patients were included. All patients had a completely edentulous maxilla, with a crestal horizontal width of <3–4 mm or a crestal vertical height of <6–7 mm. The iliac bone and ascending ramus were most frequently used as grafts. Five of the six studies reported volumes of sinus inlay graft (SIG) and four reported volumes of lateral bone augmentation (LBA). Radiographic analyses of the augmented areas differed among the studies. Volume loss after bone augmentation procedures ranged from 5% to 50% for SIG and from 5% to 47% for LBA. All surgical augmentation techniques for the edentulous maxilla are prone to resorption; no procedure seemed to be superior, but some interesting observations were made.